Stair climbing robot - Syazwan, Kamaruzzaman (2009)
This project is to design and develop the prototype of stair climbing robot. The robot body frame will be design based on the shape of the human legs and has the abilities to climbing as the autonomous robot. There were three major part in constructing this robot; mechanical design, electronic circuit design and firmware design. In the mechanical part, robot chassis, servo bracket and servo connector of the robot will be constructed step by step. This robot has three legs which has two joint for every legs. Servo motor is place at every leg joint and used as the machine in robot movement. Microcontroller PIC18F4550 will be the main processor for the robot and PBasic language will be the programming language to communicate between microcontroller and servo motor. The microcontroller will send the instruction directly to the servo motor and the robot will start climbing the stair.